this is a personal web page designed to provide you with an in-depth look into my personality, hobbies, as well as my interests. It is a "comprehensive" introduction to my online persona. It also features a collection of educational videos and resources related to my favorite topics; it is therefore considered to be an all-in-one destination for those who share similar passions and want to explore them further.
it also serves as my comfort zone, where i can always return to and add/modify something whenever i feel discomforted or stressed about some certain thing(s).
brought to you by lawi, with the best regards.
have a wonderful day ♥
lawi's note:
⟨ this website is alive, and it grows as time progresses. its growth is a function of two variables, and its value is expressed as the change in time, divided by my laziness squared. ⟩
launch version: [1.0]: 9.15.24
current version: [1.0]
[1.0]
9/15/24 ⟨ essentially done with the shape of the web page, so here goes publication. ⟩9/29/24 ⟨ currently busy with school, might restart work next month. ⟩
Please note that solutions for problems beyond Calculus II are unlikely to be posted as of now, but don't let that stop you from challenging me!
CALC II, EXAMPLE 1
\[\int \sec^3(x) \, dx = ?\]
Solution: the integrand, \(\sec^3(x)\), can be rewritten as \(\sec(x) \sec^2(x)\):
\[ \int \sec^3(x) \, dx = \int \sec(x) \sec^2(x) \, dx \]
We then utilize the method of integration by parts:
Let \(du = \sec^2(x) \, dx\); \(v = \sec(x)\)
\[ \int v \, du = uv - \int u \, dv \]
\[ \int \sec(x) \sec^2(x) \, dx = \tan(x) \sec(x) - \int \tan^2(x) \sec(x) \, dx \]
\[ = \tan(x) \sec(x) - \int (\sec^3(x) - \sec(x)) \, dx \]
\[ = \tan(x) \sec(x) - \int \sec^3(x) \, dx + \int \sec(x) \, dx \]
\[ \int \sec^3(x) \, dx = \tan(x) \sec(x) - \int \sec^3(x) \, dx + \int \sec(x) \, dx \]
We see that there are two \(\int \sec^3(x) \, dx\) terms that are on opposite sides and have opposite signs; thus, we can isolate and combine them to get:
\[ 2 \int \sec^3(x) \, dx = \tan(x) \sec(x) + \int \sec(x) \, dx \]
The integral of \(\sec(x)\) is a common integral, and it is equal to \(\ln |\tan(x) + \sec(x)| + C\). Divide both sides by 2 in order to isolate the unknown:
\[ 2 \int \sec^3(x) \, dx = \tan(x) \sec(x) + \ln |\tan(x) + \sec(x)| \]
\[ \frac{1}{2} 2 \int \sec^3(x) \, dx = \frac{1}{2} \left(\tan(x) \sec(x) + \ln |\tan(x) + \sec(x)|\right) \]
\[ \therefore \int \sec^3(x) \, dx = \frac{1}{2} \tan(x) \sec(x) + \frac{1}{2} \ln |\tan(x) + \sec(x)| + C \]
CALC II, EXAMPLE 2
\[\int \frac{\sin^2(x)}{\cos^3(x)} \, dx = ?\]
Solution: since \(\tan^2(x) = \frac{\sin^2(x)}{\cos^2(x)}\), we can replace the integrand with \(\frac{\tan^2(x)}{\cos(x)}\) or \(\tan^2(x) \sec(x)\). Substituting in the latter, we get:
\[ \int \frac{\sin^2(x)}{\cos^3(x)} \, dx = \int \tan^2(x) \sec(x) \, dx \]
\[ \int \tan^2(x) \sec(x) \, dx = \int (\sec^2(x) - 1) \sec(x) \, dx = \int (\sec^3(x) - \sec(x)) \, dx \]
\[ = \int \sec^3(x) \, dx - \int \sec(x) \, dx \]
From here on, we can just substitute both integrals with their evaluations as we know them from the previous problem. However, since \(\int \sec^3(x) \, dx\) is not a common integral, we have to assume that we do not know its value. So, there is still more work to do. (Keep in mind that you can skip the following steps and use the expression from Q1/E1, if you have already solved it)
\[ \int \tan^2(x) \sec(x) \, dx = \int \sec^3(x) \, dx - \int \sec(x) \, dx \]
We can use integration by parts again to find another expression for the integral:
Let \(du = \tan(x) \sec(x) \, dx\); \(v = \tan(x)\)
\[ \int \tan^2(x) \sec(x) \, dx = \int \tan(x) \tan(x) \sec(x) \, dx = \tan(x) \sec(x) - \int \sec^3(x) \, dx \]
We then set these two expressions equal to one another:
\[ \int \sec^3(x) \, dx - \int \sec(x) \, dx = \tan(x) \sec(x) - \int \sec^3(x) \, dx \]
And once again, we see that there are two like terms with opposite signs that are on opposite sides of the equation – namely, \(\int \sec^3(x) \, dx\). And so, we isolate and combine them. We then simplify.
\[ 2 \int \sec^3(x) \, dx = \tan(x) \sec(x) + \int \sec(x) \, dx \]
\[ = \frac{1}{2} \left(\tan(x) \sec(x) + \ln |\tan(x) + \sec(x)|\right) \]
Of the two expressions we wrote for the integral, either can be used in the following substitution step. Here, we use the second equation:
\[ \int \tan^2(x) \sec(x) \, dx = \tan(x) \sec(x) - \frac{1}{2} \left(\tan(x) \sec(x) + \frac{1}{2} \ln |\tan(x) + \sec(x)|\right) \]
Simplify.
\[ = \tan(x) \sec(x) - \frac{1}{2} \tan(x) \sec(x) - \frac{1}{2} \ln |\tan(x) + \sec(x)| \]
\[ = \frac{1}{2} \tan(x) \sec(x) - \frac{1}{2} \ln |\tan(x) + \sec(x)| \]
\[ \therefore \int \frac{\sin^2(x)}{\cos^3(x)} \, dx = \frac{1}{2} \tan(x) \sec(x) - \frac{1}{2} \ln |\tan(x) + \sec(x)| + C \]
CALC II, EXAMPLE 3
\[\int e^x \sin(x) \, dx = ?\]
Solution: integrate by parts.
Let \(du = e^x \, dx\); \(v = \sin(x)\)
\[ \int e^x \sin(x) \, dx = e^x \sin(x) - \int e^x \cos(x) \, dx \]
\[ = e^x \sin(x) - e^x \cos(x) + \int -e^x \sin(x) \, dx \]
\[ \int e^x \sin(x) \, dx = e^x \sin(x) - e^x \cos(x) - \int e^x \sin(x) \, dx \]
\[ 2 \int e^x \sin(x) \, dx = e^x \sin(x) - e^x \cos(x) \]
\[ \int e^x \sin(x) \, dx = \frac{1}{2} \left(e^x \sin(x) - e^x \cos(x)\right) \]
\[ \therefore \int e^x \sin(x) \, dx = \frac{1}{2} e^x (\sin(x) - \cos(x)) + C \]
CALC II, EXAMPLE 4
\[\int \frac{1}{x^2 - x - 1} \, dx = ?\]
Solution: complete the square on the denominator, and factorize:
\[ x^2 - x - 1 = x^2 - 1 - \left(\frac{5}{4} - \frac{1}{4}\right) = x^2 - x + \frac{1}{4} - \frac{5}{4} = \left(x - \frac{1}{2}\right)^2 - \frac{5}{4} \]
\[ \int \frac{1}{x^2 - x - 1} \, dx = \int \frac{1}{\left(x - \frac{1}{2}\right)^2 - \frac{5}{4}} \, dx \]
Let \(u = x - \frac{1}{2}\), hence \(du = dx\)
\[ \int \frac{1}{\left(x - \frac{1}{2}\right)^2 - \frac{5}{4}} \, dx = \int \frac{1}{u^2 - \frac{5}{4}} \, du \]
The denominator is now a difference of squares, and so we factorize to get two linear factors. We then integrate using partial fractions and the fact \(\int \frac{1}{l} \, dl = \ln |l|\) to get the final answer.
\[ \int \frac{1}{u^2 - \frac{5}{4}} \, du = \int \frac{1}{\left(u - \frac{\sqrt{5}}{2}\right)\left(u + \frac{\sqrt{5}}{2}\right)} \, du \]
\[ \int \frac{1}{\left(u - \frac{\sqrt{5}}{2}\right)\left(u + \frac{\sqrt{5}}{2}\right)} \, du = \int \frac{A}{u - \frac{\sqrt{5}}{2}} \, du + \int \frac{B}{u + \frac{\sqrt{5}}{2}} \, du \]
Thus:
\[ A \left(u + \frac{\sqrt{5}}{2}\right) + B \left(u - \frac{\sqrt{5}}{2}\right) = 1 \]
Setting \(u = \frac{\sqrt{5}}{2}\) gives \(\sqrt{5} A = 1\) so \(A = \frac{1}{\sqrt{5}}\), and setting \(u = -\frac{\sqrt{5}}{2}\) gives \(-\sqrt{5} B = 1\) so \(B = -\frac{1}{\sqrt{5}}\).
\[ \int \frac{A}{\left(u - \frac{\sqrt{5}}{2}\right)} \, du + \int \frac{B}{\left(u + \frac{\sqrt{5}}{2}\right)} \, du = \frac{1}{\sqrt{5}} \int \frac{1}{u - \frac{\sqrt{5}}{2}} \, du - \frac{1}{\sqrt{5}} \int \frac{1}{u + \frac{\sqrt{5}}{2}} \, du \]
\[ = \frac{1}{\sqrt{5}} \ln \left| u - \frac{\sqrt{5}}{2} \right| - \frac{1}{\sqrt{5}} \ln \left| u + \frac{\sqrt{5}}{2} \right| \]
\[ = \frac{1}{\sqrt{5}} \left( \ln \left| x - \frac{1 + \sqrt{5}}{2} \right| - \ln \left| x - \frac{1 - \sqrt{5}}{2} \right| \right) \]
\[ = \frac{1}{\sqrt{5}} \ln \left| \frac{2x - 1 + \sqrt{5}}{2x - 1 - \sqrt{5}} \right| \]
\[ = \frac{1}{\sqrt{5}} \ln \left| 1 + \frac{2 \sqrt{5}}{2x - 1 - \sqrt{5}} \right| \]
\[ \therefore \int \frac{1}{x^2 - x - 1} \, dx = \frac{1}{\sqrt{5}} \ln \left| 1 + \frac{2 \sqrt{5}}{2x - 1 - \sqrt{5}} \right| + C \]